Pengaruh Pendekatan Logoterapi dalam Mengurangi Perilaku Konsumtif pada Mahasiswa FEBI UIN Raden Fatah Palembang : Penelitian - Suryati; Hartika Utami Fitri; Nyiayu Nabilah Choiril Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The student phase is a transitional period toward adulthood characterized by emotional, social, and economic independence. During this stage, many students exhibit consumptive behavior influenced by modern lifestyles, social media, and the need to follow trends. Excessive consumptive behavior can lead to financial imbalance and low self-control. This study aims to determine the effect of the logotherapy approach in reducing consumptive behavior among students of the Faculty of Islamic Economics and Business (FEBI) at UIN Raden Fatah Palembang. The study employed a quantitative approach with a quasi-experimental nonequivalent control group design. The sample consisted of 11 students selected through purposive sampling and divided into two groups: six students in the experimental group and five in the control group. The research instrument was a Likert-scale questionnaire measuring consumptive behavior, administered during the pretest and posttest stages. Data were analyzed using the Wilcoxon Signed Rank Test through SPSS version 26 to examine differences before and after the treatment. The results showed that the average consumptive behavior score in the experimental group significantly decreased from Mean (SD) = 121.6 (9.6) to 43.3 (3.6). The control group also experienced a decrease from Mean (SD) = 115.1 (11.4) to 62.8 (15.9), but the reduction was not significant. The Asymp. Sig. (2-tailed) value of 0.027 < 0.05 indicates a significant difference before and after the intervention in the experimental group. Thus, it can be concluded that logotherapy is effective in reducing students’ consumptive behavior by strengthening their sense of meaning in life and enhancing self-awareness in making consumption decisions.